EFEKTIVITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK PADA PEMBELAJARAN MATEMATIKA - utami, adisty arisma (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
Realistic Mathematics Education (PMR) is an approach to mathematics education adopted from Realistic Mathematics Education (RME) which has been developed in the Netherlands since 1970. PMR tends to provide explanations related to realistic things, so that students can easily digest the learning delivered by educators . This study aims to conduct a literature review related to the effectiveness of realistic mathematics education (PMR) in learning mathematics. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by documenting and reviewing all articles related to mathematics education in the period 2010 –2020. The articles used in this study were 30 accredited national and international journal articles obtained from Google Schoolar, Research Gate, SINTA, DOAJ, and Scopus. Based on this research, it was found that Realistic Mathematics Education (PMR) is able to improve learning outcomes and can improve many students' mathematical abilities. Starting from the ability of intuition, mathematical problem solving ability, connection and communication skills of students. Keywords: Realistic Mathematics Education, Mathematics Learning, Systematic literature Review